Recent Advancements in the Loading and Modification of Therapeutic Exosomes - Xu, Mengqiao; Yang, Qianhao; Sun, Xiaodong; Wang, Yue (Frontiers in Bioengineering and Biotechnology, 2020)
Exosomes have a rapid development of bio-nanoparticles for drug delivery and confluent advances in next-generation diagnostics, monitoring the progression of several diseases, and accurate guidance for therapy. Based on their prominent stability, cargo-carriage properties, stable circulating capability, and favorable safety profile, exosomes have great potential to regulate cellular communication by carrying variable cargoes into specific site. However, the specific loading strategies and modification methods for engineered exosomes to enhance the targeting ability are unclear. The clinical application of exosomes is still limited. In this review, we discuss both original and modified exosomes for loading specific therapeutic molecules (proteins, nucleic acids, and small molecules) and the design strategies used to target specific cells. This review can be used as a reference for further loading and modification strategies as well as for the therapeutic applications of exosomes.